Agriculture in modern landscapes: A factor hindering or facilitating development? - Razpotnik Visković, Nika; Komac, Blaž (Acta geographica Slovenica, 2018)
Agriculture plays an important role in both protecting and developing farmland. In Slovenia, the main reasons for this loss are urbanization and the implementation of large development projects that require the destruction of fertile farmland. About 3000 ha of farmland has been lost each year since Slovenia’s independence. The importance of agriculture and farmland is touched upon in this special issue of Acta geographica Slovenica. The authors focus on management of farmland, analyse the development potential for agriculture, observe the changes in the landscape by remote sensing, soil quality and its pollution, and land cover as an element of biodiversity. They draw attention to the lack of participation in spatial planning procedures and the question of the importance of agriculture and jobs in this sector in national economy. This introductory paper brings a short analysis of how the issue of farms’ spatial constraints and moving farm structures to new locations is perceived by municipal offices, nature parks, and the Slovenian Chamber of Agriculture and Forestry and its regional offices.